Analysis Of Risk Faktors For Work Occupational Accidents In Fishermen On Lae-Lae Island - Patandung, Lismawati; Thamrin, Yahya; Wahyu, Atjo; Naiem, M. Furqaan; Amiruddin, Ridwan (Journal of Neonatal Surgery, 2025)
Background: Indonesia's expanding fishing sector poses serious occupational dangers because of dangerous working conditions, erratic weather patterns, and insufficient safety procedures, all of which have an adverse effect on the productivity and health of fishermen. Research Objectives: The purpose of this study is to examine the risk factors that influence the frequency of work-related accidents among Lae-Lae Island fishermen. Methods: There were 68 controls and 34 cases (work-related accidents) among the 102 fisherman who participated in this case-control research. Questionnaires and in-depth interviews were used to gather data, which looked at factors such age, duration of service, working hours, weariness, PPE use, and slippery floor conditions. The chi-square test and logistic regression were used for the analysis. Results: Bivariate analysis revealed that work accidents were significantly correlated with age (OR=3.125; p=0.028), duration of service (OR=2.731; p=0.048), weariness (OR=12.436; p=0.000), usage of personal protective equipment (OR=11.200; p=0.000), and slippery floor conditions (OR=5.018; p=0.000). However, there was no significant correlation between accidents and length of service (p=0.119). The most significant factors, according to multivariate analysis, were weariness (p=0.000) and not wearing personal protective equipment (p=0.000). Conclusion: The two biggest risk factors for mishaps among fisherman on Lae-Lae Island are occupational exhaustion and failure to wear personal protective equipment. Accident hazards are also increased by young age and slick flooring. Reducing accidents in the fishing industry requires rules that encourage the use of personal protective equipment (PPE), OHS training, and increased awareness.